Characterization of a Novel Acetogen Clostridium sp. JS66 for Production of Acids and Alcohols: Focusing on Hexanoic Acid Production from Syngas - Kim, Joongsuk; Kim, Ki-Yeon; Ko, Ja Kyong; Lee, Sun-Mi; Gong, Gyeongtaek; Kim, Kyoung Heon; Um, Youngsoon (Biotechnology and bioprocess engineering, 2022)
Acetogen bacteria have been spotlighted to produce fuels and chemicals from CO, H 2 , and CO 2 , main components of waste gas from the steel industry and syngas derived from lignocellulose and plastics. The production of C2∼C4 acids/alcohols from syngas has been widely studied; however, there are much less studies on the production of C6 or higher acids/alcohols due to the limited number of acetogen producing C6 or higher carbon compounds. In this study, we report a newly isolated strain Clostridium sp. JS66 that has the ability to produce C2, C4, and C6 acids/alcohols from syngas and glucose. This isolate exhibited 99.9% 16S rRNA similarity and 64.5% digital DNA-DNA hybridization value to Clostridium carboxidivorans P7 T , a known C6 acid/alcohol-producing acetogen. Characterization of gas fermentation using CO:CO 2 :H 2 [30:30:40] was carried out at different temperature (25∼37°C), initial pH (5.5∼7.0), agitation speed (50∼150 rpm), and total pressure (100∼150 kPa). When the agitation speed decreased from 150 rpm to 100 rpm at 150 kPa, hexanoic acid production significantly increased from 0.20 g/L to 0.47 g/L. Notably, the production of hexanoic acid was slightly higher at 100 kPa and 125 kPa than at 150 kPa, despite the lower supply of syngas. Moreover, the chain elongation tendency to form C6 acid/ alcohol was enhanced at lower pressures. These results demonstrate that Clostridium sp. JS66 has the potential to produce C6 compounds from syngas, extending a spectrum of C6-producing acetogen.